Effect of heat treatment on hydrogen permeation behaviour of AISI 4135 steel under splash zone conditions. (2nd April 2016) - Qu, W.; Huang, Y.; Yu, X.; Lu, D.; Zheng, M.; Marco, R. De
Abstract : Effect of heat treatment on the hydrogen permeation behaviour of AISI 4135 steel was studied by electrochemical method under simulated splash zone conditions. The hydrogen permeation current reached maximum at dry stage and the amount of hydrogen permeated showing a maximum in sixth cycle. Moreover, it was found that the amount of hydrogen permeated through specimen with bainitic microstructure was lower than that in other specimens. The average value of charge transfer resistances for heat treated specimens A, B, C and D exhibit no significant differences under nature sea water film. Moreover, the heat treatments have no prominent impact on corrosion products from the X-ray diffraction (XRD) pattern and SEM analysis. Therefore, the differences in hydrogen permeation behaviours were mainly attributed to the microstructures of specimens other than the differences in corrosion behaviour.